Pentalogía de Cantrell: Reporte de un caso de padres consanguíneos (2010)
Pentalogy of Cantrell is a syndrome evidencing five anomalies: a midline, upper abdominal wall abnormality; lower sternal defect; anterior diaphragmatic defect; diaphragmatic pericardial defect, and congenital abnormalities of the heart. Its prevalence is one in every 65,000 live births and a survival rate that is low if the fall the five defects are present or the gravity of the cardiac anomalies. It may be diagnosed during the first trimester obstetric ultrasound. For postnatal care, emission-computed tomography and magnetic resonance imaging is recommended for a clear definition of the extent of the defect and to design a course of corrective surgery. Herein, a case of pentology of Cantrell is reported for a child offspring of consanguineous parents.